2007
DOI: 10.1074/jbc.m703812200
|View full text |Cite
|
Sign up to set email alerts
|

Mitofusin 2 Protects Cerebellar Granule Neurons against Injury-induced Cell Death

Abstract: Of the GTPases involved in the regulation of the fusion machinery, mitofusin 2 (Mfn2) plays an important role in the nervous system as point mutations of this isoform are associated with Charcot Marie Tooth neuropathy. Here, we investigate whether Mfn2 plays a role in the regulation of neuronal injury. We first examine mitochondrial dynamics following different modes of injury in cerebellar granule neurons. We demonstrate that neurons exposed to DNA damage or oxidative stress exhibit extensive mitochondrial fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
155
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(164 citation statements)
references
References 34 publications
(55 reference statements)
6
155
0
2
Order By: Relevance
“…In other studies overexpression of Mfn2 and the rat homologue Fzo1 reduced cytochrome c release and apoptosis (Jahani-Asl et al, 2007;Sugioka et al, 2004) while in a fourth study, overexpression of Mfn1, Mfn2 or Opa1 had no effect on cytochrome c release or apoptosis (Sheridan et al, 2008). Importantly, the authors of the latter study demonstrated that cells displaying fused phenotypes still lost cytochrome c in response to pro-apoptotic stimuli, indicating that Bax/Bakdependent pore formation can still occur in fused mitochondria.…”
Section: Accepted M Manuscriptmentioning
confidence: 88%
See 1 more Smart Citation
“…In other studies overexpression of Mfn2 and the rat homologue Fzo1 reduced cytochrome c release and apoptosis (Jahani-Asl et al, 2007;Sugioka et al, 2004) while in a fourth study, overexpression of Mfn1, Mfn2 or Opa1 had no effect on cytochrome c release or apoptosis (Sheridan et al, 2008). Importantly, the authors of the latter study demonstrated that cells displaying fused phenotypes still lost cytochrome c in response to pro-apoptotic stimuli, indicating that Bax/Bakdependent pore formation can still occur in fused mitochondria.…”
Section: Accepted M Manuscriptmentioning
confidence: 88%
“…Within a similar time frame, mitochondria fragment from filamentous tubules into numerous small punctate particles (Frank et al, 2001;Gao et al, 2001;Jahani-Asl et al, 2007;Lee et al, 2004;Sheridan et al, 2008; Figure 2). These fragmented mitochondria often collapse from an extended network covering the majority of the cell, into a clustered perinuclear…”
Section: Mitochondrial Fission During Apoptosismentioning
confidence: 88%
“…Accordingly, over-expression of proteins involved in mitochondrial fusion prevented mitochondrial fragmentation and cell death in cerebellar granule neurons treated with H 2 O 2 (Jahani- Asl et al, 2007;Jahani-Asl et al, 2011). The mitonetwork response to oxidative stress seemed to be dose-dependent, as higher concentrations or higher exposure times to H 2 O 2 increased the mitochondrial fragmentation extent and cell death rates Jahani-Asl et al, 2007;Jendrach et al, 2008). In agreement, lower H 2 O 2 doses induced mitochondrial hyperfusion associated to decreased Fis1 expression levels and augmented Mfn1 and Mfn2 .…”
Section: The Feedback Loop Between Ros Production and Mitochondrial Dmentioning
confidence: 99%
“…Different cultured cells, including neurons, under oxidative stress due to NO or H 2 O 2 treatment showed extensive mitochondrial network fragmentation and increased cell death (Barsoum et al, 2006;Yoon et al, 2006;Jahani-Asl et al, 2007;Jendrach et al, 2008). Although the precise mechanisms by which oxidative stress modulates mitochondrial dynamics are not well understood, some authors suggested that ROS could modulate the expression levels and post-traslational modifications of the proteins involved in mitochondrial dynamics.…”
Section: The Feedback Loop Between Ros Production and Mitochondrial Dmentioning
confidence: 99%
See 1 more Smart Citation